OPTIMASI PENGGUNAAN GARAM ELEKTROLIT SEBAGAI PENGENTAL SAMPO BENING CAIR - Yulia Kurniawati; Supriyono Eko Wardoyo; Ridha Arizal (JURNAL SAINS NATURAL, 2015)
Optimization Use of Electrolyte Salt as a Thickenerin of Clear-Liquid Shampoo          A wide variety of activities undertaken by humans to meet their needs. They are needed cleaning which makes the body refreshed and become the body protected from various kinds of diseases. One sample is the cleaning shampoo. Simply in shampoo manufacturing process only the addition of materials in water as a solvent. The ingredients that are added generally include surfactants, binding agents, foaming agents, antibacterial, pH regulators, fragrances, dyes, and thickeners.The last process of manufacture of shampoo is setting viscosity. Usually, a substance used as a thickener are electrolyte salts such as sodium chloride (NaCl). However, some manufacturers of similar products using strong electrolyte salt such as sodium sulfate (Na2SO4), magnesium chloride (MgCl2), and calcium chloride (CaCl2) as a thickener. The electrolyte salts have a greater degree of dissociation compared with a weak electrolyte salts.Analysis of optimization of the use of the electrolyte salt to clear viscous liquid shampoo was performed in which the electrolyte salt used was NaCl, KCl, Na2SO4, CaCl2, and NaHSO4. Each of these electrolyte salts were added to the liquid shampoo preparations as much as 0; 0.5; 1.5; 2.5; 3.5; 4.5; 5.5; 6.5; and 7.5%. All treatments were tested the viscosity, organoleptic (color and odor), pH, and density at 250 C. Based on the research that had been done could be concluded that the best salt that could be used to clear liquid shampoo formulation  was NaCl at a concentration above 3.5%.Key words: Shampoo, electrolyte salts, surfactants ABSTRAK          Berbagai macam kegiatan dilakukan oleh manusia untuk memenuhi kebutuhannya. Dibutuhkan suatu pembersih yang menjadikan badan segar kembali dan menjadikan tubuh terhindar dari berbagai macam penyakit. Salah satu pembersih dimaksud adalah sampo. Secara sederhana proses pembuatan sampo meliputi penambahan bahan-bahan dengan air sebagai pelarutnya. Bahan-bahan yang ditambahkan pada umumnya meliputi surfaktan, zat pengikat, zat pembusa, antibakteri, pengatur pH, pewangi, pewarna, dan pengental.Proses terakhir dari pembuatan sampo adalah pengaturan kekentalan. Biasanya zat yang digunakan sebagai pengental adalah garam elektrolit seperti natrium klorida (NaCl). Namun beberapa perusahaan pembuat produk sejenis menggunakan garam elektrolit kuat lain seperti natrium sulfat (Na2SO4), magnesium klorida (MgCl2), dan kalsium klorida (CaCl2) sebagai pengental. Garam-garam elektrolit tersebut memiliki derajat disosiasi yang lebih besar dibandingkan dengan garam-garam elektrolit lemah.Analisis optimasi penggunaan garam elektrolit terhadap kekentalan sampo bening cair dilakukan dimana garam elektrolit yang digunakan adalah NaCl, KCl, Na2SO4, CaCl2, dan NaHSO4. Masing-masing garam elektrolit tersebut di tambahkan ke dalam sediaan sampo cair sebanyak 0; 0,5; 1,5; 2,5; 3,5; 4,5; 5,5; 6,5; dan 7,5 %. Semua perlakuan di lakukan uji kekentalan, organoleptik (warna dan bau), pH, dan Bobot Jenis pada suhu 25 0 C. Berdasarkan hasil penelitian yang telah dilakukan dapat disimpulkan bahwa garam terbaik yang dapat digunakan untuk formulasi sampo bening cair adalah NaCl yaitu pada konsentrasi diatas 3,5%.Kata Kunci : Sampo, Garam Elektrolit, Surfaktan